2015
DOI: 10.1097/jom.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Aluminum and Alzheimer Disease

Abstract: Objective:We conducted a meta-analysis to systematically quantify the association between occupational exposure to aluminum and risk of Alzheimer disease (AD). Methods: Electronic database searches were conducted up to March 2015 for controlled studies. Study quality was assessed using the Newcastle-Ottawa Scale. Results: Three retrospective case-control studies, involving 1056 participants, met the criteria for inclusion. All studies used surrogate informants to ascertain exposure. Occupational aluminum expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Al has been shown to be particularly dangerous for the functioning of the central nervous system, causing cognitive and neurodegenerative disorders. Many studies have shown that exposure to Al can cause neuropsychiatric and neurological symptoms, as well as diseases such as Alzheimer’s disease, risk of cognitive impairment, dementia, allergic conditions, inflammatory skin lesions, and a higher risk of developing lung cancer or bladder cancer [ 64 , 65 , 66 , 67 ]. Yoshimasu et al found higher concentrations of Al in the brain of victims of amyotrophic lateral sclerosis (ALS) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al has been shown to be particularly dangerous for the functioning of the central nervous system, causing cognitive and neurodegenerative disorders. Many studies have shown that exposure to Al can cause neuropsychiatric and neurological symptoms, as well as diseases such as Alzheimer’s disease, risk of cognitive impairment, dementia, allergic conditions, inflammatory skin lesions, and a higher risk of developing lung cancer or bladder cancer [ 64 , 65 , 66 , 67 ]. Yoshimasu et al found higher concentrations of Al in the brain of victims of amyotrophic lateral sclerosis (ALS) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have observed higher levels of Al in the circulation of AD patients [16][17][18][19][20][21][22][23], whereas B. Bobba reported lower levels of Al in serum (p < 0.05) [24], and other studies demonstrated no significance of Al level between AD and control [25,26]. Moreover, several meta-analyses of Al reported inconsistent results [27][28][29]. In addition, only a few of studies reported significant changes in the levels of Hg, Pb, and Cd.…”
Section: Introductionmentioning
confidence: 99%
“…This proved that DPP6 was associated with some neurological diseases, including cognitive diseases and memory impairment [ 41 , 42 , 43 , 44 , 45 , 47 , 51 ]. Some studies also mentioned that exposure to Al would be a potential factor in the development of Alzheimer’s disease, but the causal relationship was still controversial [ 52 , 53 , 54 , 55 ]; however, our finding showed that there was an association between Al in plasma, DPP6 , and eGFR. To our knowledge, there were few studies that explained the indirect effect of DPP6 on eGFR.…”
Section: Discussionmentioning
confidence: 43%